Prinsip Kerja Sama Tindak Tutur Direktif dan Ekspresif pada Dialog antar Tokoh dalam Film Ajari Aku Islam Sutradara Deni Pusung - Eka Fauziah; Herwandi (UIR Press, 2022)
This study aims to describe, analyze, and interpret the principle of cooperation between directive and expressive speech acts in dialogue between characters in the film Ajari Aku Islam directed by Deni Pusung. The method used in this research is descriptive method. Data collection techniques used in this study were observation, documentation, listening, and note-taking techniques. The results showed that of the 118 utterances that the writer found, there were 72 utterances of directive speech acts, 46 utterances of expressive speech acts, and 161 utterances that met the maxim of cooperative principle in directive speech acts, and 106 data of utterances that met the maxim of cooperative principle in speech acts. expressive. Based on the results of this study, it can be concluded that directive and expressive speech acts are widely used in almost all utterances spoken by the figures in the film Ajari Aku Islam directed by Deni Pusung. Meanwhile, when viewed from the use of the maxim of the cooperative principle, the overall forms of directive and expressive speech acts in the speeches of these figures fulfill the whole. This shows that the speech of the characters in the film Ajari Aku Islam has fulfilled the aspects of speech contained in pragmatic studies, so it can be stated that film is a form of literary work that allows it to contain great pragmatic power